Digital screen exposure and emotional symptoms in preschool children: mediation by parent–child relationship and moderation by peer relationships - Xu, Yongqi; Qiao, Lei (Frontiers in Psychology, 2025)
IntroductionWith the rapid development of information technology, emerging electronic media are widely used in various settings where children are present. At the same time, excessive screen exposure has been associated with various emotional symptoms in preschool children.MethodsThis study employed a questionnaire survey to collect data from 7,239 parents of preschool children in Pu’er City, China. After rigorous data screening, 6,623 valid responses were retained for analysis. The collected data were then analyzed using SPSS 25.0 for descriptive and inferential statistics, and Hayes’ PROCESS 4.0 was used to test the mediation and moderation models involving digital screen exposure, the parent-child relationship, peer relationships, and emotional symptoms in preschool children.ResultsThe results indicated that digital screen exposure was significantly associated with emotional symptoms (β = 0.2351, p < 0.01). Specifically, higher levels of screen exposure were associated with more severe emotional symptoms, and this association was mediated by the parent-child relationship (indirect effect = 0.06, 95% CI [0.03, 0.08]). Peer relationships moderated the association between digital screen exposure and emotional symptoms (interaction effect = −0.22, p < 0.01) and between digital screen exposure and the parent-child relationship (interaction effect = −0.12, p < 0.01).DiscussionThis study provides a comprehensive theoretical framework to understand the associations among digital screen exposure, emotional symptoms, and social relationships in preschool children. It highlights the potential importance of the parent-child relationship and peer relationships in buffering negative associations related to digiatl screen exposure.